THE INFLUENCE OF MINIMUM WAGE AND POPULATION SIZE ON INCOME DISTRIBUTION DISPARITY AND COMMUNITY WELFARE IN REGENCIES/CITIES OF BALI PROVINCE - Ni Kadek Lia Ratna Dewi; Ni Nyoman Reni Suasih (Adisam Publisher, 2025)
Bali Province, as one of the provinces in Indonesia, experiences income distribution disparity across its regencies and cities. Uneven income distribution negatively affects the overall welfare of the population in the province. This study aims to: (1) Analyze the influence of minimum wage and population size on income distribution disparity; (2) Analyze the influence of minimum wage, population size, and income distribution disparity on community welfare; and (3) Analyze the indirect influence of minimum wage and population size on community welfare through income distribution disparity. The data used are secondary data obtained from the Bali Provincial Statistics Agency (BPS), with a total of 135 observation points. The analytical method employed is path analysis. The results of the study show that: (1) Minimum wage and population size have no significant effect on income distribution disparity; (2) Minimum wage, population size, and income distribution disparity have a positive and significant effect on community welfare; (3) Minimum wage and population size do not have an indirect effect on community welfare through income distribution disparity.